Bilateral thalamic bleed and cerebral venous sinus thrombosis in Japanese encephalitis. (7th January 2015) - Mokkappan, Sudhagar; Basheer, Aneesh; Iqbal, Nayyar; Chidambaram, Saranya
Abstract : Japanese encephalitis (JE) is a potentially serious form of viral encephalitis with varied clinicoradiological manifestations. We report the case of a 19-year-old girl admitted with headache, vomiting and altered sensorium in the absence of fever, whose cerebrospinal fluid analysis showed lymphocytic pleocytosis with significant protein content and positive serum IgM JE antibodies. MRI with venography revealed bilateral thalamic haemorrhage and cerebral venous sinus thrombosis. Although thalamic hypodensities are a well-described feature, thalamic haemorrhage and cerebral venous thrombosis are distinctly rare in JE. This report highlights the role of imaging in cases of encephalitis in general and JE in particular, in the early detection of uncommon manifestations that may complicate these diseases.